2018
DOI: 10.1186/s12887-018-1182-z
|View full text |Cite
|
Sign up to set email alerts
|

Total and regional bone mineral and tissue composition in female adolescent athletes: comparison between volleyball players and swimmers

Abstract: BackgroundExploring the osteogenic effect of different bone-loading sports is particular relevant to understand the interaction between skeletal muscle and bone health during growth. This study aimed to compare total and regional bone and soft-tissue composition between female adolescent swimmers (n=20, 15.71±0.93 years) and volleyball players (n=26, 16.20±0.77 years).MethodsDietary intake was obtained using food frequency questionnaires. Body size was given by stature, sitting height, and body mass. Six skinf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 34 publications
1
19
0
Order By: Relevance
“…Fat distribution has been referred to the variation of fat across human body, which commonly was classified into arms, legs, and trunk [12][13][14]. It was observed that the national level volleyball players had lower BF than those of regional level, and both had lower BF and more even distribution of fat than non-athletes [12].…”
Section: Introductionmentioning
confidence: 99%
“…Fat distribution has been referred to the variation of fat across human body, which commonly was classified into arms, legs, and trunk [12][13][14]. It was observed that the national level volleyball players had lower BF than those of regional level, and both had lower BF and more even distribution of fat than non-athletes [12].…”
Section: Introductionmentioning
confidence: 99%
“…There are several studies that have researched the body composition of female volleyball players ( Nikolaidis, 2013 ; Visnes & Bahr, 2013 ; Ćopić et al, 2014 ; Paz et al, 2017 ; Valente-Dos-Santos et al, 2018 ). These studies have analysed differences between volleyball and other sports, between female volleyball players and untrained individuals, body composition in relation to the game position of the players, the effect of training on body composition and the occurrence of injuries, or the effect of body composition on the physical ability of players.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, although there is a growing body of evidence pointing to a positive relationship between regular physical activity (PA) and bone health, it is still not sufficiently clear whether swimming as a sport is associated with BMD in young adults of both sexes. 13,[16][17][18] Given the above, the main purpose of this study was to verify and compare the BMD levels of different body areas of swimming athletes of both sexes, comparing them with a control group made up of healthy university non-athletes, with ages and characteristics similar to those of the swimmers.…”
Section: Introductionmentioning
confidence: 99%